استخدام أدوات ضبط الجودة في مراقبة مياه الشرب: تحليل مؤشرات pH وTDS- حالة دراسية بمدينة صبراتة (Comprehensive Journal of Science, 2025)
This study aims to evaluate the drinking water quality in two areas of Sabratha (Al-Alalaqa) by analyzing samples from an industrial and a household desalination unit, focusing on two key indicators: pH and TDS, before and after desalination. The research problem arises from increasing challenges in ensuring the quality of drinking water due to the diversity of domestic and industrial water sources, the potential for physical and chemical contamination, and the limited use of modern statistical tools in monitoring water quality.Ninety samples were collected over 45 days according to Libyan and international standards. Results showed that pH values before desalination were close to neutrality, with a slight decrease afterward, while TDS levels significantly improved after desalination and met the permissible limits Quality control charts indicated that desalination operations were generally stable with some minor deviations. The study highlights the importance of integrating laboratory analysis with statistical quality tools to ensure safe water and reduce health risks. Continuous monitoring and technician training were recommended to enhance regulatory performance and achieve sustainable safe water delivery